Development of Digital Learning Materials Utilizing the Kvisoft Flipbook Maker Application for Indonesian Language Instruction - Hasanah H; Erwin Rahayu Saputra (Indonesian Journal of Primary Education, 2023)
The advancement of science and technology has exerted a profound influence on education. Concurrently with the evolving times and the era of globalization, marked by the rapid proliferation of products and the utilization of information technology, one such manifestation is the creation of learning media through the utilization of the Kvisoft Flipbook Maker application, which constitutes a digital book—a virtual presentation of educational materials. This application transforms the appearance of PDF files into an engaging format resembling a conventional book. The research's objective is to develop Indonesian language learning media in Primary Schools, with the aim of enhancing the quality of education to captivate student interest in learning. Data collection was carried out through observation. The research methodology employed belongs to the category of research and development (RD). The research procedure adopts the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The findings of the research affirm that the Development of Digital Books Using the Kvisoft Flipbook Maker Application in Indonesian Language Education can serve as an alternative solution to support students' learning in the era of the fourth industrial revolution. By harnessing this audiovisual medium, learning becomes more captivating, communicative, interactive, and significantly influences students' comprehension and learning outcomes. Moreover, students are motivated to cultivate a passion for learning, making it easier for them to grasp the conveyed material.